Effect of walking and running on the cardiorespiratory system, muscle injury, and the antioxidant system after 30 min at the walk-run transition speed - Verlengia, R.; de Castro Cardoso, L.; de Araujo, G.; Gonelli, P.; dos Reis, I.; Gobatto, C.; de Lima Montebelo, M.; Newsholme, Philip; de Castro Cesar, M. (2012)
This study evaluated aerobic capacity and physiological stress during walking and running at the optimal energy transition speed (OETS) in 10 young men with a mean age of 24.2 ± 2.04 yrs. The subjects underwent five cardiorespiratory treadmill tests; one test to determine the maximal aerobic capacity and four submaximal tests. Two submaximal tests were incremental walking or running tests to determine the subjects’ optimal energy transition speeds, and the other two tests were walking or running on a treadmill for 30 min at OETS. Creatine kinase and antioxidant enzyme levels were determined before and immediately after the tests. The findings indicate no significant difference (P>0.05) when running was compared to walking at the OETS. Creatine kinase and antioxidant enzyme levels were not different (P>0.05). The results indicate that walking at the individual OETS may provide benefits to the cardiorespiratory system with little physiological stress in active young men.